The Effect of Liquidity, Operational Efficiency, and Profitability on Dividend Policy - Andralie Wijaya; Neneng Susanti (Return : Study of Management, Economic and Bussines, 2025)
The dividend policy, proxied by dividend payout ratio, of conventional commercial banks in Indonesia from 2019 to 2023 showed a downward trend, giving a negative sentiment to the market. The purpose of this study is to analyze the effect of liquidity, operational efficiency, and profitability on dividend policy applied by conventional commercial banking companies listed on the Indonesia Stock Exchange between 2019 and 2023. This study uses a quantitative approach with panel data regression method. Secondary data were taken from the annual financial statements of 11 conventional commercial banking companies, which were selected through purposive sampling. Data analysis was performed using EViews 13 software. The results show that liquidity has a negative and significant influence on dividend policy, operational efficiency also has a negative and significant impact, while profitability shows a positive and significant influence on dividend policy. This study suggests that companies balance loan distribution and third-party funds for liquidity while efficiently managing cash flow, reducing operating costs, and diversifying revenue to enhance profitability and dividend policy. This study provides valuable insights for managers and investors in making decisions related to dividend policy amidst changing economic dynamics. Further research is expected to explore other variables that may be influential in a broader context.